3(7x-4)=15y

Simple and best practice solution for 3(7x-4)=15y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(7x-4)=15y equation:


Simplifying
3(7x + -4) = 15y

Reorder the terms:
3(-4 + 7x) = 15y
(-4 * 3 + 7x * 3) = 15y
(-12 + 21x) = 15y

Solving
-12 + 21x = 15y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 21x = 12 + 15y

Combine like terms: -12 + 12 = 0
0 + 21x = 12 + 15y
21x = 12 + 15y

Divide each side by '21'.
x = 0.5714285714 + 0.7142857143y

Simplifying
x = 0.5714285714 + 0.7142857143y

See similar equations:

| F(x)=50-10(x) | | ax+a=2b | | 0.8W+6.6=1 | | -7n-16=4n+18 | | 0.8x-6.4=0.8 | | 11x^2-12x+3=0 | | (9b-6)-4(2b+1)=-3 | | 15n=675 | | 8x-6=6x+7 | | ln(7x-8)=-5 | | a+ax=2a | | 675n=15 | | 2.3U+3.1=-1.5 | | 6x-2(5x+1)=2x+4 | | -9.9(z-8.7)=9.1 | | x+48=28 | | 15(x-1)+4(x+3)=2(7+x) | | 30=12x | | 8(x-1)+17(x-3)=4(4x-9)+4 | | 2x+36-2x=0 | | -2(t-5)+4t=6t-9 | | 4x+25x+13=96 | | x^8-16x^6+38x^5+96x^4-640x^3-1024=0 | | 0.03+0.025x=1.28 | | -2(t-1)+8t=3t-3 | | 2*y*x=13 | | 55+32+x=180 | | y-4=-9(x+4) | | -3(v-9)=7v+47 | | 5(y-9)=7 | | 2yx=13 | | Y=8x^3+4x^2-10x+3 |

Equations solver categories